Dosimetric and biological comparisons of single planning and double plannings for bilateral lung cancer SBRT planning based on the Cyber-Knife system - Guo, Xueling; Su, Huanfan; Wan, Fuying; Zhao, XianZhi; Cao, Tingting; Dai, Zhitao; Zhang, HuoJun (Frontiers in Oncology, 2022)
Objective The aim is to investigate the influence of single planning (Plan S) and double plannings (Plan D) on bilateral lung cancer stereotactic body radiation therapy planning from the perspective of dosimetry and biology respectively. Methods Cases with bilateral lung cancer patients who had undergone SBRT with the Cyber-Knife were enrolled, and a single planning and double plannings were designed in the Multiplan@4.2 treatment planning system equipped with the Cyber-Knife system. The single plan was to optimize the two target volumes in a separate plan, while the dual plan is to optimize two target volumes respectively in two separate plans, then perform dose superposition. Then based on the dosimetric results, the biological parameters were calculated. Thus the quality of SBRT plans for those bilateral lung cancer designed by the two methods were compared and evaluated according to the dosimetric and biological results. Results The dose distribution of both planning target volumes and surrounding organs at risk in Plan S and Plan D could meet the clinical prescription requirements. The target conformity index and the new conformity index of PTV were closer to 1 in the Double plannings, and the dose gradient GI in the Plan D was smaller than Plan S. For organs at risks, the doses received by the Plan D were relatively small. In terms of biological models, for the equivalent uniform dose of normal lung tissue, heart and esophagus, the Plan D was 6.51% (P=0.045), 19.8% (P=0.022), 27.08% (P>0.05) lower than Plan S respectively. The results showed that the equivalent uniform dose of normal tissue in the Plan D was lower relative to Plan S. Conclusions Dosimetric and biological results show that both the use of Plan D have an advantage of protecting normal tissues, and it was suggested that to design double plannings for bilateral lung cancer stereotactic body radiation therapy planning based on Cyber-Knife in the clinical practice.